Adaptive Governance System through Multi-Stakeholder Partnerships for Natural Resource Conservation in Serangan Island, Denpasar City - Amelia, Chori; Paturusi, Syamsul Alam; Merit, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2019)
This research aims to understand environmental partnerships that have built in Serangan Island, Denpasar, to understand the governance systems based on environmental partnerships in Serangan Island, Denpasar, and analyze adaptive capacity of those governance systems to changes in socioeconomic and environmental conditions in Serangan Island, Denpasar. This research is conducted in the settlements and tourism areas outside the BTID tourism area in Serangan Island, Denpasar, on December 2018 until Februari 2019, using qualitative approach is used through indepth interviews to sixteen informans, which have particular roles in natural resource conservation in Serangan Island, Denpasar, which include conservation and utilization of turtles, coral reefs, sea biota, and many types of governance and partnerships in Serangan Island. Result shows that the government and business partnerships were initiated from provision of tourism infrastructure which was developed into wider partnerships with NGOs and communities in the area of turtle conservation, while collaborative governance in the shape of community-based coastal resources management in Serangan Island. Meanwhile, adaptive co-management was developed through devolution of partial responsibility of turtle’s conservation and utilization to local communities through various deals and MoUs. Result also shows that adaptive capacity of Serangan Islanders has developed towards resilience to changes of environmental and socioeconomic conditions. Two recommendations are advised to natural resource managers in Serangan Island. Firstly, robust data collection and supervision systems needs to be developed for governance of turtles, coral reefs, and sea biota. Secondly, social learning through dialogue, reflexions, and evaluation needs to be implemented to reassess the outdated governance practices.